1993
DOI: 10.1016/0014-5793(93)81430-8
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial genome on its way to the nucleus: different stages of gene transfer in higher plants

Abstract: The vast majority of mltochondrial proteins are in all eukaryotes encoded in the nuclear genomes by genes which have been transferred from the original endosymbiont. DNA as well as RNA was and is exchanged between organelles. A functionally successful mformation transfer, however, requires complex structural and regulatory alterations of the concerned gene. The recently identified variations of the information content in mitochondrial genomes of different plant species represent different stages of the transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 148 publications
(61 citation statements)
references
References 36 publications
0
61
0
Order By: Relevance
“…We have experimentally shown that this long presequence cannot be replaced by another mitochondrial targeting signal in soybean (16). Thus, in addition to the usual requirements for gene transfer (31), Cox2 in legumes requires a unique tripartite mitochondrial targeting signal that is cleaved in a process unique to legumes (16). In this study, we show that cox2 gene transfer in legumes requires an additional step, involving a reduction in local hydrophobicity of the first transmembrane region.…”
Section: Discussionmentioning
confidence: 73%
“…We have experimentally shown that this long presequence cannot be replaced by another mitochondrial targeting signal in soybean (16). Thus, in addition to the usual requirements for gene transfer (31), Cox2 in legumes requires a unique tripartite mitochondrial targeting signal that is cleaved in a process unique to legumes (16). In this study, we show that cox2 gene transfer in legumes requires an additional step, involving a reduction in local hydrophobicity of the first transmembrane region.…”
Section: Discussionmentioning
confidence: 73%
“…Evolutionary Considerations-The transfer of cox2 genes from the mitochondria to the nucleus in the Chlamydomonad algae satisfies many of the criteria proposed by Brennicke et al (41) and Claros et al (42) for this event: acquisition of a region encoding a mitochondrial-targeting sequence (at least for cox2a), altered codon usage, acquisition of a polyadenylation signal, and diminished ϽHϾ and mesoH of the protein products. In addition, any mitochondrial cox2 genes that presumably existed have been eliminated, suggesting that this transfer occurred early in evolution.…”
Section: Cox II Is Encoded By Two Distinct Nuclear Genes In Thementioning
confidence: 99%
“…Since the first demonstration of organellar sequence embedded in nuclear DNA [9], numts have been described in several mammalian species, as well as over 70 other eukaryotes [10][11][12]. The varying level of homology between these sequences and the present-day mitochondrial genome, as well as population and family polymorphisms, indicates that the nuclear transfer of mtDNA is an ongoing process [13][14][15][16][17][18][19][20][21]28].…”
Section: Introductionmentioning
confidence: 99%